1981
DOI: 10.21273/jashs.106.4.443
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Set and Seed Number from Self- and Cross-pollinated Highbush (4x) and Rabbiteye (6x) Blueberries1

Abstract: Fruit set from self-pollination averaged 67% in 4x highbush type complex (blueberry cultivars derived from at least 5 species including Vaccinium corymbosum L.) as compared to 18% in 6x rabbiteye (V. ashei Reade) cultivars. Fruit set from cross-pollination within highbush averaged 82% as compared to 47% in rabbiteye. Seed per berry from self-pollination averaged 3.9 in highbush and 1.5 in rabbiteye. Seed per berry from cross-pollination within highbush averaged 11.2 as compared to 8.5 within rabbiteye. Cross-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This raises the possibility that fertility levels in both selfing and outcrossing are under similar genetic control, dependent on parental levels of inbreeding and relatedness, and, ultimately, the genetic constitution of the resulting zygote. Our calculations from data presented by El-Agamy et al (8 ) show that a significant correlation between selfed and outcrossed seed yield also exists among four Florida highbush cultivars (r = 0.63) and seven hexaploid cultivars (r = 0.86).…”
Section: Discussionmentioning
confidence: 50%
“…This raises the possibility that fertility levels in both selfing and outcrossing are under similar genetic control, dependent on parental levels of inbreeding and relatedness, and, ultimately, the genetic constitution of the resulting zygote. Our calculations from data presented by El-Agamy et al (8 ) show that a significant correlation between selfed and outcrossed seed yield also exists among four Florida highbush cultivars (r = 0.63) and seven hexaploid cultivars (r = 0.86).…”
Section: Discussionmentioning
confidence: 50%
“…The results of this study are consistent with previous pollination experiments with highbush, lowbush (V. angustifolium Ait. ), and rabbiteye (V. ashei Reade) blueberries, in which increasing seed number per berry improves fruit set, increases berry size, and decreases the days from pollination to ripening (Aalders and Hall, 1961;Bailey, 1938;Coville, 1921;Darrow, 1941;El-Agamy et al, 1981;Gupton, 1984;Jackson et al, 1972;Knight and Scott, 1964;Krebs and Handcock, 1988;Meader and Darrow, 1947;Moore et al, 1972;Rabaey and Luby, 1988;Vander Kloet and Lyrene, 1987;White and Clark, 1938). Two trends are clear from the literature, however: a) The cultivated Vaccinium spp.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Mainland et al (11) found that T ifblue' fruit set averaged only 16% when plants were caged to prevent cross-pollination, compared with 78% set when openpollinated. Similarly, El-Agamy et al (6) found low self compatibility among most rabbiteye cultivars in Florida. Fruit set for open-pollinated plants ranged from 75% for 'Southland' (10) to 12.8% for 'Tifblue' rabbiteye cultivars in Florida (5).…”
mentioning
confidence: 90%
“…Yield is a function of many factors, including flower bud number, flower number per bud, and fruit size (8); however, the percentage of fruit set may be important in Florida and similar areas, where plants may receive less than optimum chill units (2). Many factors affect fruit set of rabbiteye blueberry, including cross-compatibility (6), presence and activity of pollinators (5), water stress (1,2), plant nutrition (2), growth regulators (4,11), and chill unit accumulation (2). Rabbiteye blueberries are generally self-unfruitful and set a very low percentage of flowers when not adequately cross-pollinated (6,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation